COMMUNICATION PREFERENCE, ANXIETY AND PROFICIENCY AMONG GRADE 10 SECONDARY STUDENTS - Richel John G. Teodosio, MAT, (European Journal of Life Safety and Stability (2660-9630), 2021)
This is the researcher’s response on the needs of the ESL learners for effective delivery of instruction and understanding the learner’s need especially in communication. This descriptive-correlational research was conducted to determine the communication preference, anxiety, and proficiency of 99 grade 10 students in Junior High School coming from the Father Julian C. Rago Memorial National High School District of Balete in the Division of Aklan. To determine the communication preference, level of anxiety and proficiency, researchers-made questionnaires were used. The frequency count, percentage, mean, standard deviation, ANOVA and Pearson r were employed as statistical tools and set at 0.05 level of significance for the analysis of data. Overall, the communication preferences of the Grade 10 secondary students have “moderately preferred” and most of the Grade 10 students used oral communication as preferred means of communication. On the other hand, communication anxiety of the Grade 10 students are “moderately severe” and the level of communication proficiency of the Grade 10 are “good.” There is a significant difference in communication proficiency. Moreover, there is no significant difference in communication proficiency among the level communication anxiety among the Grade 10 students. There is a significant relationship among Communication Preferences, Anxiety and Communication Proficiency. However, there is no significant relationship in Communication Anxiety and Proficiency among Grade 10 secondary students.